Inhibition of matrix metalloproteinases: a troubleshooting for dentin adhesion - Izadora Quintela Souza de Moraes; Ticiano Gomes do Nascimento; Antonio Thomás da Silva; Lilian Maria Santos Silva de Lira; Abhishek Parolia; Isabel Cristina Celerino de Moraes Porto (Restorative Dentistry & Endodontics)
Matrix metalloproteinases (MMPs) are enzymes that can degrade collagen in hybrid layer and reduce the longevity of adhesive restorations. As scientific understanding of the MMPs has advanced, useful strategies focusing on preventing these enzymes' actions by MMP inhibitors have quickly developed in many medical fields. However, in restorative dentistry, it is still not well established. This paper is an overview of the strategies to inhibit MMPs that can achieve a long-lasting material-tooth adhesion. Literature search was performed comprehensively using the electronic databases: PubMed, ScienceDirect and Scopus including articles from May 2007 to December 2019 and the main search terms were “matrix metalloproteinases”, “collagen”, and “dentin” and “hybrid layer”. MMPs typical structure consists of several distinct domains. MMP inhibitors can be divided into 2 main groups: synthetic (synthetic-peptides, non-peptide molecules and compounds, tetracyclines, metallic ions, and others) and natural bioactive inhibitors mainly flavonoids. Selective inhibitors of MMPs promise to be the future for specific targeting of preventing dentin proteolysis. The knowledge about MMPs functionality should be considered to synthesize drugs capable to efficiently and selectively block MMPs chemical routes targeting their inactivation in order to overcome the current limitations of the therapeutic use of MMPs inhibitors, i.e., easy clinical application and long-lasting effect.